THE URGENCY OF HUMANITIES AND SOCIAL STUDIES IN INDONESIAN EDUCATION (RESPONDING TO HUMANITIES TWILIGHT IN JAPAN) - Mohammad Liwa Irrubai (Universitas Islam Negeri (UIN) Mataram, 2020)
This article aims to explain the importance of humanities studies in Indonesian education, as a response to the humanities twilight pessimism in Japan. Afterward how its effect toward the continuity of humanities and social studies in Indonesian education. The study uses a qualitative approach using library research. The data analysis method applied was in meta-analysis. Based on the data and analysis, it was explained that it is reasonable if Japan wants to erase Humanities and Social Studies because of the decreasing population numbers, the lack of manpower, industrial competition and dependency to China and other countries, and the influence of Shinto teaching and Shingaku Concept inspiring Prime Minister Abe in focusing on Engineering education. This also replies to the Fukuyama’s concern in the emergence of post-historic where there is no longer art and philosophy. Meanwhile, based on Constitution number 20 of 2003 on National Education system that Humanities and Social Studies is still important in achieving national education objectives as well as shaping Indonesian people thoroughly because it still having national leadership crisis, corruption emergency, drug emergency, economy that has not got better yet. It is also to create the humane people and fight for Indonesian survival. Soekarno, Mohammad Hatta, and other figures indicating that Humanities and Social Studies affect humanity, the spirit in awakening, struggle, resistance toward oppression, patriotism, and justice